1997
DOI: 10.1021/ja9517072
|View full text |Cite
|
Sign up to set email alerts
|

The Naphthylcarbene Potential Energy Hypersurface

Abstract: The naphthylcarbene potential energy surface (PES) was examined ab initio, employing self-consistent field (SCF), second-order perturbation theory (MP2), and density functional (Becke3LYP) methods in conjunction with 6-31G*, DZ, DZP, and 6-311+G* basis sets. All stationary structures were characterized by vibrational frequency analyses at the Becke3LYP/6-31G* level; final energies were evaluated at the Becke3LYP/6-311+G*//Becke3LYP/6-31G* + ZPVE level. Cyclobuta[de]naphthalene is the global minimum on this par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(101 citation statements)
references
References 49 publications
(70 reference statements)
3
98
0
Order By: Relevance
“…Based on the MAD (mean average deviation) values with reference to experimental quantities, it was concluded that B3LYP is clearly superior to MP2 and other density functionals 40–44. Moreover, for carbenes, B3LYP gives a better description of the singlet state 45–53. We therefore expect the B3LYP calculations to be more reliable.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the MAD (mean average deviation) values with reference to experimental quantities, it was concluded that B3LYP is clearly superior to MP2 and other density functionals 40–44. Moreover, for carbenes, B3LYP gives a better description of the singlet state 45–53. We therefore expect the B3LYP calculations to be more reliable.…”
Section: Resultsmentioning
confidence: 99%
“…The infrared intensities were determined from the gradients of the dipole moment 71–73. All the calculated vibrational frequencies are scaled by a factor of 0.95 to correct the anharmonicity effects in this work 69–76. All the electronic structure calculations were carried out using the TURBOMOLE program suite 66–70…”
Section: Computational Detailsmentioning
confidence: 99%
“…Flash vacuum pyrolysis of either the 1-or 2-diazomethylnaphthalenes gave this isomer as a major product. Xie et al, 24 have also found that the cyclobutanaphthalene lies ca. 28 kcal mol Ϫ1 below the benzobicycloheptatriene 6 at the B3LYP/6-311ϩG* level, and that this isomer represents the global minimum on the C 11 H 8 energy surface.…”
Section: Matrix Isolation Photochemistry Of 3-chloro-3-(1-naphthyl)di...mentioning
confidence: 95%